2005
DOI: 10.1111/j.1600-6143.2005.01065.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Liver Transplantation Advisable for Isoniazid Fulminant Hepatitis in Active Extrapulmonary Tuberculosis?

Abstract: Antituberculous treatment is a well-known cause of fulminant hepatic failure (FHF). This could lead to liver transplantation as the only possible treatment, which on the other hand could be contraindicated due to active tuberculosis. The risk of aggressive dissemination of the disease after transplantation is not clearly determined by the current second-line antituberculous therapies. We report a case of vertebral tuberculosis treated with rifampin, isoniazid and pyrazinamide. He developed an FHF that was trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…Meyers et al have shown that continued therapy with ethambutol and fluoroquinolones is effective in liver transplant patients who show hepatotoxicity to the conventional drug regimen (36). Similarly, in those patients who are transplanted secondary to fulminant hepatic failure from either conventional therapy or treatment of latent tuberculosis, successful continuation of treatment with second-line TB drugs has been reported (16,17,39,40). It must be noted that the efficacy of second-line regiments is yet to be proven in large scale clinical trials, and as mentioned previously, even first-line agent therapy for active TB on the posttransplant scenario is associated with high morbidity.…”
Section: Discussionmentioning
confidence: 96%
“…Meyers et al have shown that continued therapy with ethambutol and fluoroquinolones is effective in liver transplant patients who show hepatotoxicity to the conventional drug regimen (36). Similarly, in those patients who are transplanted secondary to fulminant hepatic failure from either conventional therapy or treatment of latent tuberculosis, successful continuation of treatment with second-line TB drugs has been reported (16,17,39,40). It must be noted that the efficacy of second-line regiments is yet to be proven in large scale clinical trials, and as mentioned previously, even first-line agent therapy for active TB on the posttransplant scenario is associated with high morbidity.…”
Section: Discussionmentioning
confidence: 96%
“…37 Although the use of standard ATT may be considered when TB occurs after solid organ transplantation and notably after LT, the reintroduction of drugs able to provoke ALF is difficult to justify after transplantation. With the aim of quantifying the risk of toxicity with INH, Barcena et al 38 took biopsy samples from liver grafts to determine the genotype of cytochrome P450-2 E1 and the status of N-acetyl transferase, and they showed that these 2 components play an important role in INH toxicity. However, this is not practicable in routine practice, and the use of an anti-TB regimen that excludes hepatotoxic drugs and for which the efficacy has been demonstrated remains the best alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Given such an important agent to treat TB, some recommendations prefer the use of rifampin for SOT with TB with at least two-fold to five-fold increase of doses of calcineurin inhibitors and close monitoring of their serum levels [7 && , 26,27]. There are two possible scenarios for patients with preexisting TB undergoing transplantation: one is that patients develop acute hepatic failure after anti-TB regimens requiring liver transplantation [9][10][11][28][29][30][31][32][33][34][35][36], and the other is that those with unrecognized TB receive transplantation [11,37]. Table 1 …”
Section: Treatment Of Active Tuberculosismentioning
confidence: 99%